HILLSLOPE TOPOGRAPHIC AND HYDROLOGIC EFFECTS ON OVERLAND FLOW AND EROSION - Huang C.; Gascuel-Odoux C.; Cros-Cayot S. (My University, 2002)
Variability in surface condition occurs at different spatial and temporal scales. Locally, surface conditions interact with soil components and determine the dynamic of surface sealing, biomass, and roughness. At the hillslope scale, conditions at the surface vary with the topographic position that can cause different hydrologic regimes and erosion. This paper presents our efforts in quantifying how hillslope position and moisture condition affected runoff generation and sediment production. In the field, we monitored runoff and sediment productions from a hillslope under natural conditions. Sediment production under seepage condition was quantified in a laboratory dual-box system under simulated rainfall. Field results showed that variability in runoff and sediment production could be attributed to topographically induced and localized surface variations in addition to seasonal changes in rainfall pattern and crop canopy. Based on rainfall pattern and changes in surface conditions, three different stages of runoff and sediment productions were identified in an annual cycle. Laboratory experiments in soil moisture gradient (i.e., seepage vs. drainage) effects on erosion showed that drainage conditions limited sediment detachment while seepage conditions enhanced rilling. These results showed a close linkage between surface moisture condition and erosion process, and consequently, the dominant sediment regime. These different methodologies improved the understanding of runoff and erosion processes occurring at the hillslope and the role of topographic position and hydrology on these processes.
Keywords: SOIL EROSION; TOPOGRAPHIC POSITION; RUNOFF; SEDIMENT; SPATIAL AND TEMPORAL VARIABILITY